2022
DOI: 10.1155/2022/5636903
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Medical Needs and Early Referral of Pediatric Atopic Dermatitis: An Expert Modified Delphi Consensus from Saudi Arabia

Abstract: Atopic dermatitis (AD) is a chronic skin disease with increasing prevalence worldwide. It is characterized by pruritic eczematous lesions, affecting up to 20% of the children and negatively impacting their quality of life. Guidelines for AD management are available worldwide, but specific guidelines for pediatric AD in Saudi Arabia are lacking. This consensus document aims to identify the needs for the diagnosis and management of pediatric AD in Saudi Arabia by gathering the opinions and recommendations of key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…A frequent childhood ailment that may persist into adulthood is eczema. Kids with eczema are prone to develop food allergies, asthma, & allergic rhinitis.. (Alradaddi et al, 2022). Due to the close relationship between early-onset eczema & food allergies, preventing dermatitis may help prevent food allergies.…”
Section: Literatures Reviewmentioning
confidence: 99%
“…A frequent childhood ailment that may persist into adulthood is eczema. Kids with eczema are prone to develop food allergies, asthma, & allergic rhinitis.. (Alradaddi et al, 2022). Due to the close relationship between early-onset eczema & food allergies, preventing dermatitis may help prevent food allergies.…”
Section: Literatures Reviewmentioning
confidence: 99%
“…A study conducted in the United States found that longer EBF was associated with a lower risk of AD (OR 0.89 per month; 95% CI 0.82-0.97). 8 A study conducted in Japan found that EBF for at least six months was associated with a lower risk of AD (OR 0.70; 95% CI 0.52-0.93). 9 While the protective effect of breastfeeding against AD has been reported in many studies, there is limited research on this topic in Saudi Arabia, particularly in the Al Madinah region (AL-Hijaz area of Western Saudi Arabia).…”
Section: Introductionmentioning
confidence: 99%
“…IgA also modulates the gut microbiota, which is thought to be involved in the development of AD. 8 However, the evidence for this association is inconsistent, and few studies have examined this association among Saudi infants.…”
Section: Introductionmentioning
confidence: 99%